2015
DOI: 10.1117/12.2083654
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced detection of dentinal lesions in OCT images using the RKT transformation

Abstract: Several studies have shown that optical coherence tomography (OCT) can be used to measure the remaining enamel thickness and detect the location of subsurface lesions hidden under the sound enamel. The purpose of this study was to develop algorithms to enhance the visibility of subsurface structures such as hidden occlusal lesions and the dentinal-enamel junction. Extracted teeth with natural occlusal lesions were imaged with OCT with and without added high index fluids. A Rotating Kernel Transformation (RKT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The steps involved in converting the 3D CP‐OCT images into the mean values of the lesion depth ( L d ) and integrated reflectivity over the lesion depth (Δ R ) in the ROI are described in reference and shown graphically in the flowchart of that paper. For speckle noise reduction, signals not exceeding four standard deviations from the mean background noise floor were reduced to the mean background value and a Gaussian blur smoothing algorithm was applied using a 5 × 5 pixel convolution kernel . Finally, a modified rotating kernel transformation (RKT) emphasizing more on horizontal edges than on vertical edges was applied to each 2D b‐scan image to further increase signal‐to‐noise ratio thereby increasing the optical penetration .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The steps involved in converting the 3D CP‐OCT images into the mean values of the lesion depth ( L d ) and integrated reflectivity over the lesion depth (Δ R ) in the ROI are described in reference and shown graphically in the flowchart of that paper. For speckle noise reduction, signals not exceeding four standard deviations from the mean background noise floor were reduced to the mean background value and a Gaussian blur smoothing algorithm was applied using a 5 × 5 pixel convolution kernel . Finally, a modified rotating kernel transformation (RKT) emphasizing more on horizontal edges than on vertical edges was applied to each 2D b‐scan image to further increase signal‐to‐noise ratio thereby increasing the optical penetration .…”
Section: Methodsmentioning
confidence: 99%
“…For speckle noise reduction, signals not exceeding four standard deviations from the mean background noise floor were reduced to the mean background value and a Gaussian blur smoothing algorithm was applied using a 5 × 5 pixel convolution kernel . Finally, a modified rotating kernel transformation (RKT) emphasizing more on horizontal edges than on vertical edges was applied to each 2D b‐scan image to further increase signal‐to‐noise ratio thereby increasing the optical penetration . In the edge‐detection approach, the enamel edge, and the lower lesion boundary were determined by applying an edge locator .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various imaging analysis methods have been developed for enhancing structures and edges, speckle reduction and denoising OCT images [14–16]. Last year we demonstrated that image processing methods can further improve the visibility of subsurface occlusal lesions [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies show that the visibility of hidden occlusal lesions can be significantly increased by use of optical clearing agents and image analysis methods. 19,20 Optical clearing agents have routinely been used in biological microscopy and have found recent application in clinical imaging, including OCT. 21,22 We postulate that OCT is ideally suited for monitoring and improving the diagnosis of QOCs, and methods can be developed to enhance the visibility of hidden subsurface lesions. Even though the optical penetration of near-IR light can easily exceed 7 mm through sound enamel to image lesions on proximal surfaces with high contrast, 23 the large increase in light scattering due to demineralization 24 typically limits optical penetration in highly scattering lesions (also dentin and bone) to 1 to 2 mm, thus cutting off the OCT signal before it reaches the dentinal-enamel junction (DEJ).…”
Section: Introductionmentioning
confidence: 99%